2017
DOI: 10.1021/acs.orglett.7b01826
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Hydroamination of Alkoxyallenes with Azole Heterocycles: Examples and Mechanistic Proposal

Abstract: Palladium-catalyzed regio- and enantioselective addition of azole heterocycles to alkoxyallenes was developed (up to 92% yields and up to 94% ee). DFT calculations suggest a new Pd(0)-driven mechanistic pathway proceeding through protonation of the Pd-coordinated allene (4-PdL2), which develops a strongly nucleophilic character at the central C atom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…Ionization of intermediate III followed by outersphere nucleophilic attack with pyrazole anion on the C3 carbon affords the desired allylic pyrazole 3 and regenerates Pd(0) complex I. In support of a Pd(0) pathway, Huang and Rutjes' 24 computations have shown that the formation of the Pd(II)-H complex from [Pd( 3 -C3H5)Cl]2 is kinetically infeasible at temperatures up to 80 C. In line with this, we do not observe Pd-H when studying a mixture of [Pd( 3 -C3H5)Cl]2 with ligand in d8toluene.…”
Section: Table 1 Ligand Effects On Asymmetric Pyrazole Hydroaminationmentioning
confidence: 98%
“…Ionization of intermediate III followed by outersphere nucleophilic attack with pyrazole anion on the C3 carbon affords the desired allylic pyrazole 3 and regenerates Pd(0) complex I. In support of a Pd(0) pathway, Huang and Rutjes' 24 computations have shown that the formation of the Pd(II)-H complex from [Pd( 3 -C3H5)Cl]2 is kinetically infeasible at temperatures up to 80 C. In line with this, we do not observe Pd-H when studying a mixture of [Pd( 3 -C3H5)Cl]2 with ligand in d8toluene.…”
Section: Table 1 Ligand Effects On Asymmetric Pyrazole Hydroaminationmentioning
confidence: 98%
“…In support of a Pd 0 pathway, Huang [22] and Rutjes’ [23] computations have shown that the formation of the Pd II −H complex from [Pd(η 3 ‐C 3 H 5 )Cl] 2 is kinetically infeasible at temperatures up to 80 °C. In line with this, we do not observe Pd−H when studying a mixture of [Pd(η 3 ‐C 3 H 5 )Cl] 2 with ligand in d 8 ‐toluene .…”
Section: Figurementioning
confidence: 99%
“…The metal-catalysed intermolecular addition of other nucleophiles (e.g. amines [54][55][56][57][58][59][60][61], azides [62,63], electron-rich aromatic groups [64][65][66][67][68][69][70] and azoles [71][72][73][74]) to allenes has been widely reported. In general, allyl derivatives are obtained as the main products of the reaction when gold complexes are used.…”
Section: Introductionmentioning
confidence: 99%